The bright end of the galaxy luminosity function at z ≃ 7 from the VISTA VIDEO survey - Varadaraj, RG; Bowler, RAA; Jarvis, MJ; Adams, NJ; Haussler, B (Oxford University Press, 2023)
We have conducted a search for z ≃ 7 Lyman-break galaxies over 8.2 deg2 of near-infrared imaging from the Visible and Infrared Survey Telescope for Astronomy (VISTA) Deep Extragalactic Observations (VIDEO) survey in the XMM–Newton-Large Scale Structure (XMM-LSS) and the Extended Chandra Deep Field-South (ECDF-S) fields. Candidate galaxies were selected from a full photometric redshift analysis down to a Y + J depth of 25.3 (5σ), utilizing deep auxiliary optical and Spitzer/Infrared Array Camera (IRAC) data to remove brown dwarf and red interloper galaxy contaminants. Our final sample consists of 28 candidate galaxies at 6.5 ≤ z ≤ 7.5 with −23.5 ≤ MUV ≤ −21.6. We derive stellar masses of 9.1 ≤ log10(M⋆/M⊙) ≤ 10.9 for the sample, suggesting that these candidates represent some of the most massive galaxies known at this epoch. We measure the rest-frame ultraviolet (UV) luminosity function (LF) at z ≃ 7, confirming previous findings of a gradual decline in number density at the bright end (MUV < −22) that is well described by a double power law (DPL). We show that quasar contamination in this magnitude range is expected to be minimal, in contrast to conclusions from recent pure-parallel Hubble studies. Our results are up to a factor of 10 lower than previous determinations from optical-only ground-based studies at MUV ≲ −23. We find that the inclusion of YJHKs photometry is vital for removing brown dwarf contaminants, and z ≃ 7 samples based on red optical data alone could be highly contaminated (≳50 per cent). In comparison with other robust z > 5 samples, our results further support little evolution in the very bright end of the rest-frame UV LF from z = 5–10, potentially signalling a lack of mass quenching and/or dust obscuration in the most massive galaxies in the first Gyr.